Effect of Pollyallylamine on Alcoholdehydrogenase Structure and Activity - Kim, Aleksandr L.; Musin, Egor V.; Dubrovskii, Alexey V.; Tikhonenko, Sergey A. (Polymers, 2020)
In this article, the effect of polyallylamine (PAA) on the structure and catalytic characteristics of alcohol dehydrogenase (ADH) was studied. For this research, we used methods of stationary kinetics and fluorescence spectroscopy. It has been shown that PAA non-competitively inhibits ADH activity while preserving its quaternary structure. It was established that 0.1 M ammonium sulfate removes the inhibitory effect of PAA on ADH, which is explained by the binding of sulfate anion (NH4)2SO4 with polyallylamine amino groups. As a result, the rigidity of the polymer chain increases and the ability to bind to the active loop of the enzyme increases. It is also shown that sodium chloride removes the inhibitory effect of PAA on ADH due to an electrostatic screening of the enzyme from polyelectrolyte. The method of encapsulating ADH in polyelectrolyte microcapsules was adapted to the structure and properties of the enzyme molecule. It was found that the best for ADH is its encapsulation by adsorption into microcapsules already formed on CaCO3 particles. It was shown that the affinity constant of encapsulated alcohol dehydrogenase to the substrate is 1.7 times lower than that of the native enzyme. When studying the affinity constant of ADH in a complex with PAA to ethanol, the effect of noncompetitive inhibition of the enzyme by polyelectrolyte was observed.